Regulating capital : setting standards for the international financial system - Singer, David Andrew (Cornell studies in money., 2007)
"Financial instability threatens the global economy. The volatility of capital movements across national borders has led many observers to argue for a reformed "global financial architecture," a body of consistent rules and institutions to prevent financial crises. Yet regulators have a decidedly mixed record in their attempts to create global standards for the financial system. David Andrew Singer seeks to explain the varying pressures on regulatory agencies to negotiate internationally acceptable rules and suggests that the variation is largely traceable to the different domestic political pressures faced by regulators."--Jacket